MODEL ASESMEN AFEKTIF BERBASIS THAWAB DAN 'IQAB DALAM PENDIDIKAN AGAMA ISLAM: SEBUAH KAJIAN KONSEPTUAL - Maksum; Moh. Sahlan (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2026)
This research aims to construct an affective assessment model based on thawab and 'iqab in Islamic Religious Education (PAI). The study employs a qualitative approach with library research and conceptual approach methods. Data were collected through documentation studies from the Qur'an, Hadith, books, and scientific journal articles, then analyzed using content analysis. The findings reveal that (1) thawab and 'iqab in Islamic education serve as character development instruments grounded in the principles of justice, compassion, and behavioral improvement; (2) affective assessment in PAI still faces challenges including cognitive dominance, subjectivity, and suboptimal follow-up actions; (3) the constructed model comprises eight stages: determining indicators, data collection, analysis, behavioral classification, implementation of thawab, implementation of educative 'iqab, reflection and counseling, and continuous assessment. This model integrates modern assessment theories with Islamic educational values, transforming assessment into a continuous and transformative character development cycle. The main contribution of this research is the reconstruction of thawab and 'iqab functions as integral components of the PAI affective assessment system.